2020
DOI: 10.1186/s12888-020-02938-w
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of symptoms, ever having received a diagnosis and treatment of depression and anxiety, and associations with health service use amongst the general population in two Russian cities

Abstract: Background Little is known about the burden of common mental disorders in Russia despite high levels of suicide and alcohol-related mortality. Here we investigated levels of symptoms, self-reports of ever having received a diagnosis and treatment of anxiety and depression in two Russian cities. Methods The study population was men and women aged 35–69 years old participating in cross-sectional population-based studies in the cities of Arkhangelsk a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
1
9
1
Order By: Relevance
“…However, the World Health Organization estimates the level of depression in Russia to be 5.5% (WHO 2017), one of the highest in the world. Non-representative studies conducted in selected regions report a prevalence rate (PHQ-9 ≥ 10) equal to 10.7% in women and 5.4% in men (Cook et al 2020). The Russian context is characterized by a plethora of factors contributing to high levels of depression such as increasing poverty rate, declining standards of living, complex socio-political background (Averina et al, 2005;Cook et al 2020, World Bank 2021) and at the same time, negative attitudes toward both depression and seeking professional help (Turvey, Jogerst, Kim, Frolova, 2012; Nersessova, Jurcik, Hulsey, 2019).…”
Section: Data Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the World Health Organization estimates the level of depression in Russia to be 5.5% (WHO 2017), one of the highest in the world. Non-representative studies conducted in selected regions report a prevalence rate (PHQ-9 ≥ 10) equal to 10.7% in women and 5.4% in men (Cook et al 2020). The Russian context is characterized by a plethora of factors contributing to high levels of depression such as increasing poverty rate, declining standards of living, complex socio-political background (Averina et al, 2005;Cook et al 2020, World Bank 2021) and at the same time, negative attitudes toward both depression and seeking professional help (Turvey, Jogerst, Kim, Frolova, 2012; Nersessova, Jurcik, Hulsey, 2019).…”
Section: Data Contextmentioning
confidence: 99%
“…Non-representative studies conducted in selected regions report a prevalence rate (PHQ-9 ≥ 10) equal to 10.7% in women and 5.4% in men (Cook et al 2020). The Russian context is characterized by a plethora of factors contributing to high levels of depression such as increasing poverty rate, declining standards of living, complex socio-political background (Averina et al, 2005;Cook et al 2020, World Bank 2021) and at the same time, negative attitudes toward both depression and seeking professional help (Turvey, Jogerst, Kim, Frolova, 2012; Nersessova, Jurcik, Hulsey, 2019). National-level study representative for 20-21-year-olds report the prevalence of depression (PHQ-9 ≥ 10) at 20% for women and 12% for men (Dementeva , Smirnov, 2021).…”
Section: Data Contextmentioning
confidence: 99%
“…Similar to previous reports, our data indicated that 77.4% of women under lockdown reported symptoms of moderate anxiety, while 54.8% of the entire cohort reported symptoms of mild depression ( 15 ). It is important to note that the values for these two categories of symptoms under normal conditions among Russian women were 4 and 25%, respectively ( 31 ). We did not find a significant difference between the two age groups studied.…”
Section: Discussionmentioning
confidence: 99%
“…For each item, possible answers and respective scores were: (0) "not at all", (1) "less than half of the days", (2) "more than half of the days", and (3) "almost every day". The PHQ-9 classified depression severity according to: none (1-4 points), mild (5)(6)(7)(8)(9), moderate (10)(11)(12)(13)(14), moderately severe (15)(16)(17)(18)(19), and severe (20-27) 8 . The scale, already validated in Brazil, allows for the identification of individuals likely to develop depression 9 .…”
Section: Study Variables Measurement Of Positive Screening For Depres...mentioning
confidence: 99%
“…High heterogeneity was found across the available estimates of depression due to methodological between-study variability. In Brazil, 11 different screening tools were used to assess depression morbidity in the 27 studies analyzed by Silva et al 4 , which resulted in a high variability of estimates: 14% (95%CI: [13][14][15][16]) of depressive symptoms, 8% (95%CI: 7-10) of major depressive disorder (MDD) in the last year, and 17% (95%CI: [14][15][16][17][18][19]) of lifetime MDD. The authors advocating the need for standardization of future research with a validated tool in a nationwide survey.…”
Section: Temas Livres Free Themes Introductionmentioning
confidence: 99%